Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - Chapter 1 Review Problem Set: 60

Answer

$13$

Work Step by Step

Substituting $a= 3 $ and $b= -4 $, the given expression, $ \dfrac{2a+b}{b+6}-3b ,$ evaluates to \begin{array}{l}\require{cancel} \dfrac{2(3)+(-4)}{-4+6}-3(-4) \\\\= \dfrac{6-4}{2}+12 \\\\= \dfrac{2}{2}+12 \\\\= 1+12 \\\\= 13 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.